A bio-inspired flexible squeezing reactor for efficient enzymatic hydrolysis of lignocellulosic biomass for bioenergy production. (May 2022) - Deng, Zhichao; Liao, Qiang; Xia, Ao; Huang, Yun; Zhu, Xianqing; Qiu, Sheng; Zhu, Xun
Abstract: Wheat straw is a promising source that can be used to obtain clean energy through its bioconversion into biofuel. Enzymatic hydrolysis is considered as a key step in biofuel production. However, the poor mixing of enzymes and lignocellulosic substrates caused by the high viscosity of biomass slurry significantly astricts such a process. In this study, a novel bio-inspired flexible tube reactor was developed for enhancing mass transfer through squeezing at different parts to imitate the intestinal peristalsis. The results of the visualization experiment showed that the apparent vertical diffusion velocity at different position were about 1.4–4.2 times faster than the control without squeezing, when the concentration of model solution (carboxymethyl cellulose solution) was 5 g/L. More importantly, the apparent vertical diffusion velocity increased by 5.2 times as the concentration of model solution increased to 20 g/L at squeezing mode. When the total solid (TS) concentration of lignocellulosic slurry was increased to 7.5%, the bionic reactor showed an excellent performance on the enzymatic hydrolysis of wheat straw. The highest reducing sugar yield achieved 20.2 g/L with 71.8% of carbohydrate conversion after 170 min at 40 rpm, which was 2.1 times higher than the control without squeezing.